Literature for children in the Publishing House of I. P. Ladyzhnikov (Berlin, 1920–1930) - A. О. Anisimov (Библиосфера, 2021)
The purpose of the article is to fill the gap in the study of such an aspect of the activities of Russian-language foreign publishing houses as the release of literature for children and youth. Such activity is reflected very poorly in book research. This is primarily due to the fact that there were very few specialized publishing houses for the production of children’s literature in the Russian Diaspora, and their archives were either fragmentarily available for study or were absent altogether. At the same time, the publication of children’sliterature in Russian in the first post-revolutionary years was of great demandboth in the emigre community and in Soviet Russia, which was unable to satisfy the urgent need for such literature. The article presents the results of a search for information about the release of Russian-language children’s literature in the Russian Diaspora in the first half of the 1920s, using the example of the activities of one of the most notable emigrant enterprises – I. P. Ladyzhnikov, who was in 1906–1932 in Berlin. Being in essence a universal publishing house, it was in the 1920s actively involved in the process of publishing literature for children, having its own unique circle of authors, illustrators (both Russian and foreign), creating a specialized children’s department in its structure, publishing a children’s book in very solid volumes.